Temperature‐dependent uniaxial ratchetting of ultra‐high molecular weight polyethylene. Issue 7 (29th January 2016) - Chen, K.; Kang, G.; Lu, F.; Xu, J.; Jiang, H.
Abstract: Uniaxial stress‐controlled cyclic tests were performed on the ultra‐high molecular weight polyethylene (UHMWPE) polymer at different temperatures. The effects of stress level, stress rate, peak/valley stress hold and loading history on the ratchetting of the UHMWPE were discussed at different temperatures, and the temperature‐dependence of ratchetting was addressed. It is concluded from the experimental observations that the ratchetting of the UHMWPE depends greatly on the test temperature, and the ratchetting strain increases with the increasing temperature from −20 to 37 °C, but decreases when the temperature is equal to or higher than 60 °C in some cases. The ratchetting is also time‐dependent and increases with the increase of peak stress hold time and the decrease of stress rate. The ratchetting presents apparent loading history dependence, and previous cyclic history with higher stress level remarkably restrains the occurrence of ratchetting in the subsequent cyclic loading cases with lower stress levels, but previous cyclic history with lower stress level hardly influences the ratchetting in the subsequent cyclic loading cases with higher stress levels.